Thylakogaster namibiensis sp. nov. (Isopoda: Asellota: Janiroidea), a new species of Haplomunnidae from the southeast Atlantic deep sea - Brenke, Nils; Buschmann, Anika (Zootaxa, 2009)
Thylakogaster namibiensis sp. nov., a new deep-sea species belonging to the family Haplomunnidae Wilson, 1976 is described from the southeast Atlantic Ocean. The differences of the new species to the other species of the genus Thylakogaster Wilson and Hessler, 1974 are discussed. Main characters distinguishing T. namibiensis sp. nov. from its congeners are the presence of cuticular spines on the lateral margins of the pereonites 1–7, the low number of spines on the pleotelson, and the number of five terminal flagellar articles bearing aesthetascs on the antenna 1 of the copulatory male. The new species, T. namibiensis, is the first member of this genus found in the southeast Atlantic Ocean and at a depth of 5415 m, it is also the deepest which a member of the genus has ever been found.